The role of triglyceride glucose index in development of Type 2 diabetes mellitus. (September 2018) - Low, Serena; Khoo, Kay Chin Jonathon; Irwan, Bastari; Sum, Chee Fang; Subramaniam, Tavintharan; Lim, Su Chi; Wong, Tack Keong Michael
Abstract: Aims: Triglyceride-Glucose (TyG) is an emerging surrogate indicator of insulin resistance. We explored the role of TyG in development of Type 2 Diabetes Mellitus (T2DM) and elucidated the mechanism for the relationship. Methods: 4109 subjects without baseline T2DM participated in a community screening programme in 2013–2016. TyG was calculated as Ln[fasting triglyceride level (mg/dl) × fasting plasma glucose (FPG) (mg/dl)/2]. Outcome was T2DM defined as FPG ≥ 7.0 mmol/l; current treatment with anti-diabetes medication; and/or self-reported diabetes on follow-up screening. We used Cox proportion-hazard model to assess risk of T2DM by TyG quartiles at baseline. Binary mediation analysis was performed to examine extent of mediation by TyG between Body Mass Index (BMI) and T2DM development. Results: After 5734.23 person-years of follow-up, T2DM developed in 117 subjects with an incidence of 20.40/1000 person-years. Risk of T2DM incidence was increased with quartiles 2, 3 and 4 versus quartile 1 of TyG (adjusted HR 1.79(95%CI 0.80–3.99), 2.54 (1.18–5.49) and 4.68(2.19–10.01), Ptrend  < 0.001) across TyG quartiles. TyG accounted for 35.1% of association between BMI and T2DM development, having adjusted for potential cofounders (p < 0.001). Conclusions: TyG is potentially useful for predicting T2DM in clinical practice. It is a potential mediator of association between BMI and T2DM development.